ANALISIS FRASA ENDOSENTRIS DAN EKSOSENTRIS PADA NOVEL - Eka Gusti; Faisal Kristian (Arsil Media, 2023)
The phrase is one of the elements that fills the function in a sentence that builds a news discourse in the daily newspaper Detik.com. Phrases are divided into two groups, namely endocentric and exocentric phrases, this group of phrases fills the syntactic function in news discourse in the Daily Detik.com newspaper. These phrase groups will form a phrase structure which can be composed of words and words, words and phrases, and phrases and phrases to form a complete/complete sentence.